Conduction Mechanism of Solid Biopolymer Electrolytes System Based on Carboxymethyl cellulose - Ammonium chloride - Nur Hidayah Ahmad; Mohd Ikmar Nizam Mohamad Isa (American-Eurasian Network for Scientific Information publisher, 2024)
Volume: 9 Number: 2